Students Thinking Processes in Generalizing Patterns Based on The Personality of RIASEC Holland Theory - Nusrotul Bariyah; Jarnawi Afgani Dahlan; Seth Junior Nti (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2024)
Generalizing patterns is a fundamental mathematical skill with widespread applications. However, only 7.1% of students demonstrate high proficiency in generalizing patterns, indicating significant challenges in identifying and applying rules. This study explores the thinking processes of students who succeed and fail in generalizing linear patterns, analyzed through the lens of Holland's RIASEC personality model. Employing a qualitative phenomenological approach, data were collected through pattern generalization tests, RIASEC questionnaires, and interviews conducted with seven junior high school students in Bandung, selected based on communication skills and varied personality types. The findings reveal that students with investigative personalities are most successful, exhibiting critical thinking and problem-solving abilities aligned with pattern generalization tasks. In contrast, unsuccessful students predominantly rely on numerical data or recursive strategies without effectively connecting visual configurations. This research identifies three distinct thinking processes: focusing solely on numerical data, combining numerical data with operational adjustments, and refining generalizations using visual patterns. The study underscores the importance of leveraging visual aids and trial-and-error methods in teaching pattern generalization. Differentiated instruction, tailored to students’ cognitive and personality traits, is recommended to address diverse learning needs and enhance mathematics education quality. This study contributes to understanding the interplay between personality and cognitive strategies in mathematical problem-solving. It also emphasizes the necessity for inclusive teaching strategies that cater to varied student profiles to foster success in generalizing patterns and developing essential mathematical skills